The effect of courage on stress: The mediating mechanism of behavioral inhibition and behavioral activation in high-risk occupations - Wang, Jia; Sun, Dingyu; Jiang, Juan; Wang, Huizhong; Cheng, Xiaotong; Ruan, Qianying; Wang, Yichao (Frontiers in Psychology, 2022)
Employees in high-risk occupations are exposed to tremendous work acute stress or prolonged stress disorders that are likely to undermine the health and organizational effectiveness. Based on positive psychology, courage, which refers to behavioral approach despite the experience of fear, could buffer the negative effects on stress. However, there is little known about the mechanisms by which courage decreases the risk of stress. Motivational systems might play an underlying role in this process, as behavioral inhibition system (BIS) is inhibited and behavioral activation system (BAS) is evoked by risk or threat. The current study aimed to examine the mediating effects of behavioral inhibition and activation on the relationship between courage and stress in the high-risk occupations. This study recruited 1,761 high-risk employees aged from 18-27 (M=19.32; SD=4.14) with a cluster sampling method who completed Courage Measure, the BIS/BAS Scales and the Psychological Stress Evaluation Test. The correlation and mediation analyses examined the inter-variable correlations as well as the underlying mechanism between courage and stress. The results support the hypothesis and reveal that the behavioral inhibition mediates the association between courage and stress (Bindirect=-0.02, p＜0. 01, 95%CI=-0.03～-0.003). The behavioral activation of fun seeking mediates the association between courage and stress as well (Bindirect= -0.04, p＜0. 01, 95%CI=-0.058～-0.029). These findings suggest that behavioral inhibition and activation of fun seeking play imperative mechanism underpinning the buffering effect of courage on stress. Other theoretical and applied implications for desensitizing stress in the high-risk occupations are discussed.